Analisis Pembelajaran Daring Terhadap Hasil Belajar Siswa di SD 118178 Janji Matagor - Ayu Widya Ningsih; Handini Avantika Hsb; Masytoh Rangkuti; Yosephine Edwina; M. Perangin Angina (Publikasi Indonesia, 2022)
Conditions in the midst of a pandemic forced them to conduct online learning on the learning outcomes of elementary school students, this is in line with the statement from the United Nations, which stated that one of the sectors affected by this outbreak was the world of education. Therefore, online learning is carried out in the midst of a pandemic to see the learning outcomes of students. This research is a qualitative descriptive study which describes the analysis of online learning on student learning outcomes. The method used is interviews as a source of primary data and secondary data.